1988
DOI: 10.1037/0278-7393.14.4.709
|View full text |Cite
|
Sign up to set email alerts
|

Very long-term memories of the first year in college.

Abstract: College alumnae who had graduated 2, 12, or 22 years earlier completed questionnaires in which they recounted the first four memories to come to mind of their freshman year and provided ratings of each remembered experience. For all three alumnae groups, the temporal distribution of memories peaked in September, the beginning of college. Mean ratings of emotional intensity were high, mean ratings of surprise and life impact were below the moderate level and substantial numbers of memories had never been recoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 28 publications
5
73
2
Order By: Relevance
“…Many studies of autobiographical memory document that emotional arousal improves, rather than impairs, memory (see overview by Brewer, 1992) though sometimes only for the central details of the event (see Christianson,1992, for a review). Instead of leading to disintegration, highly emotional and (thus) distinctive events may help to keep the autobiography integrated by forming reference points for the organization of other less distinctive events (Neisser, 1982;Pillemer et al, 1988;Robinson, 1992;Rubin & Kozin, 1984;Shum, 1998). Consistent with this view, Berntsen (2001) argued that traumatic memories are likely to form multiple links to other memories in the autobiographical knowledge base and thereby become reference points for the attribution of autobiographical meaning to less distinctive experiences and for generating expectations.…”
Section: The Landmark View Of Trauma Memories In Ptsdmentioning
confidence: 51%
“…Many studies of autobiographical memory document that emotional arousal improves, rather than impairs, memory (see overview by Brewer, 1992) though sometimes only for the central details of the event (see Christianson,1992, for a review). Instead of leading to disintegration, highly emotional and (thus) distinctive events may help to keep the autobiography integrated by forming reference points for the organization of other less distinctive events (Neisser, 1982;Pillemer et al, 1988;Robinson, 1992;Rubin & Kozin, 1984;Shum, 1998). Consistent with this view, Berntsen (2001) argued that traumatic memories are likely to form multiple links to other memories in the autobiographical knowledge base and thereby become reference points for the attribution of autobiographical meaning to less distinctive experiences and for generating expectations.…”
Section: The Landmark View Of Trauma Memories In Ptsdmentioning
confidence: 51%
“…In support of this theory, Cohen and Faulkner (1988) found that 93% of vivid life memories were of either first-time experiences or of unique events. Similarly, Pillemer, Goldsmith, Panter, and White (1988) observed high memorability of first-time experiences, with 41% of participants' memories for their first year at college coming from their first month of coursework.…”
mentioning
confidence: 99%
“…The longest schemata concern a person's course of life (e.g., people go to kindergarten when they are about 4 years old), but other schemata concern shorter scales. The distribution of events in a year (Kurbat, Shevell, & Rips, 1998;Pillemer, Goldsmith, Panter, & White, 1988), a week (Gibbons & Thompson, 2001;Huttenlocher et al, 1992), or a day (people have breakfast in the morning) are examples of shorter temporal schemata. had participants date personal events on a calendar and measured the absolute error in days.…”
mentioning
confidence: 99%